Relationship between depressive symptoms and deterioration of quality of life in Peruvian First Division soccer players - Maguiña-Figueroa, Samantha (2024)
Currently, depression is estimated to affect 280 million people worldwide. Depression is related to a variety of factors such as interpersonal relationships, quality of life, loss of autonomy, and others. In recent years, football (or soccer) has gained a prominent position in the social life of the Peruvian population, leading to high expectations about the life and behavior of its athletes. Soccer has, thus, turned into a profession with numerous demands and constant pressures, which has impacted negatively the quality of life of Peruvian players. Objective: To determine the association between quality of life and depression in athletes of the Peruvian Football Federation (FPF) in the period 2019-2020. Methods: An observational, analytical, and retrospective design type of study, this is a secondary analysis of the "Situational Diagnosis of Physical, Mental, Nutritional, and Social Health of Soccer Players" project. It focused on athletes registered in all categories of the first Division of the Peruvian Football Federation. Results: Of a total of 168 participants, 54.8% (n=92) reported an inadequate quality of life, and 17.3% (n=29) had depressive symptoms according to the CESD-7 scale. In the bivariate analysis, 21.7% (n=20) of athletes with depressive symptoms reported a low quality of life. With the Poisson regression, it was found that athletes with depressive symptoms had 1,42 times more deterioration in their quality of life (95% CI 1,05-1,93). Conclusions: The quality of life of a proportion of professional soccer players in Perú, appears to be affected by demonstrable depressive manifestations.